DEVELOPING ENGLISH LEARNING MATERIALS BASED ON CONTENT-BASED APPROACH FOR NURSING STUDENTS OF STIKES PAYUNG NEGERI PEKANBARU - Wahyudi Wahyudi (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
The absence of English learning materials containing nursing topics is one of the factors that cause the students’ low mastery of English for Nursing Purposes. Thus, the learning materials need to be developed. The ADDIE model covering the phases of analysis, designing, developing, and implementation, was used to produce the content-based learning materials for nursing students of STIKes Payung Negeri Pekanbaru. Evaluation phase, however, was excluded for further research to find out the effectiveness of the product. Those phases were to explore the students’ needs; to design learning materials; to develop the design and to find out its validity; and to find out the practicality of the product. The respondents were the head of nursing program, lecturers, nursing students, and the experts of nursing contents and material development. The instruments were a set of needs analysis questionnaire, validation checklists, and questionnaire of product practicality. The findings indicated the real needs of nursing students that they prefer learning English for Nursing Purposes to General English. The nursing topics that they wanted most to learn were related to hospital, nursing care, medical treatment, diseases, and medicines. The experts’ validations approved that the product was very valid and it was proved practical in implementation phase. It is suggested that the nursing content-based learning materials can be used to improve students’ mastery of English for Nursing Purposes.